Digital Technology Adoption for Food Waste Reduction in the Downstream Supply Chain - Gbaiye, Opemipo O. (2022)
Governments and the public at large are now more conscious of the issues around food loss and waste because of extreme climate change impacts and recent disruptions in the global food network. These issues have necessitated discussions around reducing food waste, particularly in the downstream supply chain. The adoption of technology at different levels in the food supply chain has been proposed to tackle this issue, as technology can improve surplus food distribution between retailers and consumers. This research aims to reduce food waste by using a quantitative survey to identify the major factors that influence consumers’ intention to adopt technology for food waste reduction. The findings suggest that perceived enjoyment is the most significant contributor to the intention to adopt food waste reduction technology, while factors such as perceived social benefit, perceived ease of use, technology as a solution belief and perceived vulnerability were not found to impact the intention to adopt the technology. These findings can be leveraged by key players in the food supply network to drive technology adoption for surplus food distribution. The limitations and recommendations can also be used to improve the quality of future research.